Violencia de género en los trayectos cotidianos en transporte urbano en el Área Metropolitana de Monterrey - Soto Canales, Karina (UNIVERSIDAD DE SONORA, 2023)
Qualitative research generated around daily mobility and urban transportation users is scarce. This document aims to point out, from the individual, the broad behavioral spectrum (exclusion, domination, control) with respect to gender-based violence in daily journeys, the concepts gathered for the conformation of the antecedents includes urban mobility of public transport users in the Metropolitan Area of Monterrey (AMM). The methodology used defines some characteristics that typify this socio-spatial field through in-depth interviews and life stories of women, with wich tangible and intangible perceptions of the user are recovered, which allows that through content analysis (classification and content analysis) establish three predominant categories on the phenomenon of study: schedules (predictability), perception and clothing. Finally, it reflects on the practices of domination, control and subordination in the city (street, bus stop and bus) as an obstacle to the fair use and occupation of urban space, as a right to the city; the findings, in turn, suggest new possibilities for approaching the subject, as well as the redefinition of the universe of study based on other characterizations (age, economic activities, just to mention a few).